Proposal of a new semiquantitative methodology for flowslides triggering susceptibility assesment in the carbonate slope contexts of Campania (southern Italy) - Di Crescenzo, Giuseppe; De Falco, Melania; Iervolino, Vittorio Emanuele; Rinaldi, Silvana; Santangelo, Nicoletta; Santo, Antonio (Italian journal of engineering geology and environment, 2008)
Flowslides are quite frequent phenomena in Campania region and present a serious hazard to the community as evidenced by the large number of victims and the huge economic damage caused over the last few years. In this work a method for assessing the triggering susceptibility to this type of landslide is proposed. It utilizes the overlay mapping technique, has a geomorphological approach and takes into account a great quantity of morphometric data, collected from over 187 flowslides in recent years. By taking this database into account the main factors which were significant in triggering the slides were selected throughout a statistical approach and compiled at 1:5,000 scale. A numerical value (“score”) was then attributed to each predisposing factor both with a heuristic and a statistical approach. Thus the thematic maps can be weighted and overlaid by means of a GIS application, using a mathematical expression, allowing the elaboration of the landslide susceptibility map. The method was tested in the area of the Lattari Mountain ridge, which was in the past affected by various flowslides. Of a sample of 774 landslides recorded in the area by different authorities, 91% were collocated in the very high and high susceptibility classes.